2003
DOI: 10.1189/jlb.0803396
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil peptide TFF2 treatment reduces VCAM-1 expression and leukocyte recruitment in experimental intestinal inflammation

Abstract: There is evidence for a beneficial effect of trefoil peptides in animal models of gastric damage and intestinal inflammation, but the optimal treatment strategy and the mechanistic basis have not been explored thoroughly. It has been suggested that these proteins may modulate the inflammatory response. The aims of this study were to compare the protective and curative value of systemic and topical trefoil factor family (TFF)2 administration in dextran sulfate sodium-induced experimental colitis and to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…This protective effect seemed in part to be mediated via TFF-induced expression of prostaglandin-endoperoxide synthase 2. Intra colonic instillation of hTFF2 was furthermore found to reduce expression of vascular cell adhesion molecule I (VCAM-1) on endothelial cells and leucocyte adhesion to intestinal venules in this model [170], supporting an anti-inflammatory effect of the peptides. While the DSS model may be suitable to study direct epithelial damage, it lacks the chronic inflammation and involvement of the adaptive immune system characteristic for IBD.…”
Section: Effect Of Tffs In Animal Models Of Diseasementioning
confidence: 96%
“…This protective effect seemed in part to be mediated via TFF-induced expression of prostaglandin-endoperoxide synthase 2. Intra colonic instillation of hTFF2 was furthermore found to reduce expression of vascular cell adhesion molecule I (VCAM-1) on endothelial cells and leucocyte adhesion to intestinal venules in this model [170], supporting an anti-inflammatory effect of the peptides. While the DSS model may be suitable to study direct epithelial damage, it lacks the chronic inflammation and involvement of the adaptive immune system characteristic for IBD.…”
Section: Effect Of Tffs In Animal Models Of Diseasementioning
confidence: 96%
“…Several groups have reported that application of recombinant trefoils can reduce inflammatory indices in animal models of colitis (16,33,40). For example, luminal application of recombinant TFF2/spasmocytic peptide in a rat model of colitis revealed markedly accelerated colonic mucosal rebuilding and reduced inflammatory indices (40) through mechanisms that could possibly include inhibition of inducible nitric oxide synthase and NO in monocytes (17).…”
Section: Discussionmentioning
confidence: 99%
“…These secreted peptides maintain epithelial integrity, are important for protection and wound healing. They are expressed rapidly in response to injury and are up-regulated in inflammation and ulceration [52]. TFFs are GI factors that allow the healthy mucosa to restrain inflammation and live harmoniously with its abundant flora.…”
Section: Discussionmentioning
confidence: 99%